A TPU foam film based on composite material and preparation method thereof
By adding silicone-covered fibers and anti-UV toughening additives to the TPU film, combined with other modifiers, the insufficient performance problem of TPU film when used in various environments is solved, and the toughness of the film is significantly improved. Wear resistance, UV resistance and high temperature resistance extend service life.
Patent Information
- Application Number
- CN202411081455.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-08-08
AI Technical Summary
When used in various environments, existing TPU films have insufficient toughness, low high temperature resistance, and waterproof and wear resistance. At the same time, they have weak UV resistance, resulting in accelerating film aging.
Using a composite-based TPU foam film, by adding silicone-covered fibers and anti-UV toughening additives to the TPU resin, combined with environmentally friendly mist slip masterbatch, diisopropyl peroxide, and ethylene glycol diethyl ether diethyl Aminesite, foaming agent, antioxidant and flame retardant are processed through high-speed mixing and single screw extrusion molding, cooling and stretching.
It significantly improves the toughness, wear resistance, UV aging resistance, waterproofness and high temperature resistance of TPU film, extends the service life of the film, and can meet the needs of use in various environments.
Smart Images

Figure CN118580671B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a TPU foamed film based on a composite material and a preparation method thereof. Background Art
[0002] TPU material, or thermoplastic polyurethane material, is a polymer material with superior performance and environmental protection performance. It has the characteristics of thermoplastic processing. With its superior oil resistance, weather resistance, biocompatibility and light weight, it has been greatly welcomed in various fields. Due to its easy processing and environmental protection characteristics, it is often used to make TPU film and is widely used in the field of footwear manufacturing. It participates in the production of uppers, shoe covers, insoles, etc. This requires that the TPU film used needs to have excellent toughness, high temperature resistance, waterproof performance and wear resistance. It can maintain the stability of shape, size and performance in special high temperature environments, is not easy to crack, can resist ultraviolet rays when used outdoors, slow down the aging process, is waterproof and non-slip in rainy weather, is not easy to wear when worn for a long time, and is durable.
[0003] At present, ordinary TPU films are difficult to meet the requirements of footwear production in various environments. Therefore, in actual use, people often modify them. For example, the patent with announcement number CN117186623B discloses a heat-resistant and stable TPU film and its preparation method. The polyurethane and filler are mixed, melt-extruded, cooled and stretched to obtain a heat-resistant and stable TPU film. This film has excellent heat resistance, tear resistance and wear resistance, but the UV resistance of the film needs to be improved. Under long-term ultraviolet radiation, the aging process of the film will be accelerated, affecting the service life. Summary of the invention
[0004] The purpose of the present invention is to provide a TPU foam film based on a composite material and a preparation method thereof, which solves the following technical problems: (1) the problem that ordinary TPU films are not tough enough, have poor high temperature resistance, and need to improve their waterproof and wear resistance; (2) when ordinary TPU films are used outdoors for a long time, their anti-ultraviolet ability decreases, leading to film aging.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A TPU foaming film based on a composite material comprises the following raw materials in parts by weight: 60-80 parts of TPU resin, 10-15 parts of environmentally friendly mist-slip masterbatch, 5-6 parts of dicumyl peroxide, 2-3 parts of ethylene glycol diethyl ether diamine tetraacetic acid, 8-10 parts of organosilicon-coated fibers, 10-12 parts of anti-ultraviolet toughening additives, 2-3 parts of foaming agents, 1-3 parts of antioxidants, and 2-5 parts of flame retardants; the organosilicon-coated fibers are prepared by coating silicone oil on the surface of modified medical stone fibers; the anti-ultraviolet toughening additives are prepared by introducing a rosette skeleton and a benzophenone group into a polyvinyl butyral structure.
[0007] Furthermore, the hardness of the TPU resin is 88-92A; the foaming agent is any one of azodicarbonamide, p-toluenesulfonyl semicarbazide, and sodium bicarbonate; the antioxidant is any one of antioxidant 1010, antioxidant 1076, and antioxidant 168; and the flame retardant is any one of diphenyl phosphate, 2-ethylhexyl diphenyl phosphate, and tetraethyl methylene diphosphonate.
[0008] Furthermore, the method for preparing the organosilicon-coated fiber comprises the following steps:
[0009] S1: Place medical stone fiber in anhydrous ethanol, ultrasonically disperse for 10-15 minutes, introduce nitrogen, add chloroethyl isocyanate and catalyst, heat to 60-70°C for reaction for 2-3 hours, cool down, filter, wash and dry to obtain modified medical stone fiber;
[0010] S2: Place the modified medical stone fiber in deionized water, ultrasonically disperse it for 15-20 minutes, add terminal amino silicone oil and triethylamine, heat it to 80-85°C, stir it for 12-18 hours, filter it after cooling, wash it, and dry it to obtain the silicone-coated fiber.
[0011] In this scheme, under the action of a catalyst, the hydroxyl group on the surface of the medical stone fiber reacts with the isocyanate group in the structure of chloroethyl isocyanate to obtain a modified medical stone fiber with active chlorine on the surface, and then under the action of triethylamine, the active chlorine on the surface of the modified medical stone fiber reacts with the amino group in the structure of the amino-terminated silicone oil, and silicone oil is coated on the surface of the medical stone fiber to obtain an organosilicon-coated fiber. The organic matter on the surface of the organosilicon-coated fiber can enhance the compatibility of the medical stone fiber in the composite material, and the organosilicon-coated fiber is evenly dispersed in the matrix material, and the silicone oil on its surface is dispersed in the matrix to enhance the high temperature resistance and waterproof ability of the TPU film, and the cohesion of the matrix material is improved by the close combination of the fiber and the substrate, thereby improving the overall tensile strength of the TPU film, enhancing the wear resistance, and improving the durability of the TPU film.
[0012] Furthermore, in step S1, the catalyst is any one of stannous octoate and dibutyltin dilaurate.
[0013] Furthermore, in step S2, the viscosity of the amino-terminated silicone oil is 3000-10000 mPa·s.
[0014] Furthermore, the preparation method of the anti-ultraviolet toughening additive comprises the following steps:
[0015] SS1: polyvinyl butyral, 3,4,9,10-perylenetetracarboxylic dianhydride and p-toluenesulfonic acid are placed in toluene, heated to 70-75°C for reaction for 6-8h, and the product is collected after reduced pressure distillation to obtain modified polyvinyl butyral;
[0016] SS2: Modified polyvinyl butyral, 2,3,4,4'-tetrahydroxybenzophenone and p-toluenesulfonic acid are placed in N,N-dimethylformamide, the temperature is raised to react, and the product is collected after rotary evaporation to obtain an anti-ultraviolet toughening additive.
[0017] In this scheme, under the action of p-toluenesulfonic acid, the hydroxyl group in the structure of polyvinyl butyral reacts with the anhydride group in the structure of 3,4,9,10-perylenetetracarboxylic dianhydride to obtain modified polyvinyl butyral, and then under the action of p-toluenesulfonic acid, the carboxyl group in the structure of modified polyvinyl butyral reacts with the hydroxyl group in the structure of 2,3,4,4'-tetrahydroxybenzophenone to obtain an anti-ultraviolet toughening additive. The anti-ultraviolet toughening additive has good compatibility with the matrix material of the TPU film, and can effectively buffer the stress of the TPU film when impacted, improve the toughness of the TPU film, and improve the impact resistance. At the same time, a wreath skeleton and a benzophenone group are introduced into its structure, which effectively enhances the high temperature resistance and wear resistance of the TPU film, and gives the TPU film excellent anti-ultraviolet ability, improves the durability of the TPU film when used outdoors, and significantly enhances its service life.
[0018] Furthermore, in step SS1, the molecular weight of the polyvinyl butyral is 30,000-45,000.
[0019] Furthermore, in step SS2, the temperature of the temperature-raising reaction is 105-115° C., and the time is 5-8 hours.
[0020] A method for preparing a TPU foamed film based on a composite material, characterized in that it comprises the following steps:
[0021] Step 1, place TPU resin, environmentally friendly mist slip masterbatch, dicumyl peroxide, ethylene glycol diethyl ether diamine tetraacetic acid, silicone coated fiber, anti-ultraviolet toughening additive, foaming agent, antioxidant, flame retardant in a high-speed mixer, mix at a rate of 600-800r / min for 30-45min to obtain a mixture;
[0022] Step 2: Place the mixed material in a single screw extruder, extrude and shape at 180-200° C., cool and stretch to obtain a TPU composite film.
[0023] Beneficial effects of the present invention:
[0024] The present invention prepares silicone-coated fibers and anti-ultraviolet toughening additives and adds them to the base material of the TPU composite film, so that the prepared TPU composite film has excellent toughness, wear resistance, anti-ultraviolet aging ability, waterproofness and high temperature resistance, good durability, can meet the use requirements of the TPU composite film under various conditions, and has a long service life.
[0025] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0027] Figure 1 It is the thermal weight loss curve of medical stone fiber, modified medical stone fiber and organosilicon coated fiber in the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The preparation methods of the organosilicon-coated fibers and the anti-ultraviolet toughening additives in the following examples and comparative examples of the present invention are as follows:
[0030] 1. Preparation of silicone coated fibers
[0031] S1: 3g of medical stone fiber was placed in 100ml of anhydrous ethanol, and after ultrasonic dispersion treatment for 10min, nitrogen was introduced, 2.5g of chloroethyl isocyanate and 0.03g of stannous octoate were added, and the temperature was raised to 60°C for reaction for 2h. After cooling, the fiber was filtered, washed and dried to obtain modified medical stone fiber;
[0032] S2: 3.5 g of modified medical stone fiber was placed in 120 ml of deionized water, and after ultrasonic dispersion treatment for 15 min, 3.8 g of terminal amino silicone oil with a viscosity of 3000 mPa·s and 0.05 g of triethylamine were added, the temperature was raised to 80°C, stirred for 12 h, cooled, filtered, washed, and dried to obtain silicone-coated fiber.
[0033] Thermogravimetric analysis was performed on medical stone fiber, modified medical stone fiber and silicone coated fiber. Figure 1 It can be seen that the mass retention rate of medical stone fiber under high temperature is 96.8%, and the lost part is caused by the thermal decomposition of crystal water; the mass retention rate of modified medical stone fiber is 52.5%, and the lost part is caused by the thermal decomposition of chloroethyl isocyanate, a bridging agent on the surface of modified medical stone fiber; the mass retention rate of silicone-coated fiber is 23.3%, and the lost part is caused by the thermal decomposition of organic matter grafted on its surface.
[0034] By modifying the surface of the medical stone fiber and then reacting it with terminal amino silicone oil, the silicone oil is coated on the surface of the medical stone fiber to obtain silicone-coated fiber, which participates in the preparation process of TPU film and effectively enhances the toughness, waterproofness and high temperature resistance of the film, so that it can meet the use requirements of the film in various situations.
[0035] 2. Preparation of UV-resistant toughening additives
[0036] SS1: 3 g of polyvinyl butyral with a molecular weight of 30,000, 2 g of 3,4,9,10-perylenetetracarboxylic dianhydride and 0.02 g of p-toluenesulfonic acid were placed in 60 ml of toluene, heated to 70°C for reaction for 6 h, and the product was collected after reduced pressure distillation to obtain modified polyvinyl butyral;
[0037] The acid-base titration method was used to test the carboxyl content in the modified polyvinyl butyral. The specific operation was as follows: 1g of modified polyvinyl butyral was placed in 50ml of acetone solution as a sample, an excess of 0.1mol / L potassium hydroxide-ethanol standard solution was added, 1ml of phenolphthalein indicator was added, and after sufficient mixing, a 0.1mol / L hydrochloric acid standard solution was used for back titration. When the color changed significantly, a blank experiment was performed at the same time, and the volumes of the consumed potassium hydroxide ethanol standard solution and the hydrochloric acid standard solution were recorded, and the calculation was performed according to the following formula: W=45×c(V-V1)×100% / m; wherein W is the carboxyl content in the sample, %; c is the concentration of the hydrochloric acid standard solution, mol / L; V is the volume of the consumed hydrochloric acid standard solution, ml; V1 is the volume of the hydrochloric acid standard solution consumed in the blank sample, ml; m is the sample mass, g; 45 is the molar mass of the carboxyl group, g / mol; after calculation, the carboxyl content in the modified polyvinyl butyral is 7.9%.
[0038] SS2: 3.2 g of modified polyvinyl butyral, 3.5 g of 2,3,4,4'-tetrahydroxybenzophenone and 0.03 g of p-toluenesulfonic acid were placed in 80 ml of N,N-dimethylformamide, heated to 105°C for reaction for 5 h, and the product was collected after rotary evaporation to obtain an anti-ultraviolet toughening additive.
[0039] The acid-base titration method was used to test the carboxyl content in the anti-UV toughening additive. The specific detection method was the same as that of SS1. After calculation, the carboxyl content in the anti-UV toughening additive was 2.2%. The loss was due to the reaction and consumption of the carboxyl groups in the modified polyvinyl butyral structure and the hydroxyl groups in the 2,3,4,4'-tetrahydroxybenzophenone structure.
[0040] Polyvinyl butyral is modified by using 3,4,9,10-perylenetetracarboxylic dianhydride, and the wreath skeleton is grafted into the polyvinyl butyral structure to obtain modified polyvinyl butyral. The carboxyl group in the modified polyvinyl butyral structure is reacted with the hydroxyl group in the 2,3,4,4'-tetrahydroxybenzophenone structure, and then a benzophenone group is introduced into its structure to obtain an anti-ultraviolet toughening additive. Adding it to the preparation process of TPU film can effectively improve the toughness, wear resistance, high temperature resistance and anti-ultraviolet ability of the film, and significantly extend the service life of the film.
[0041] Example 1, Preparation of TPU composite film
[0042] Step 1, 60g of TPU resin with a hardness of 88A, 10g of environmentally friendly mist-slip masterbatch, 5g of diisopropylbenzene peroxide, 2g of ethylene glycol diethyl ether diaminetetraacetic acid, 8g of silicone-coated fiber, 10g of anti-ultraviolet toughening additive, 2g of azodicarbonamide, 1g of antioxidant 1010, and 2g of diphenyl phosphate were placed in a high-speed mixer and mixed at a rate of 600r / min for 30min to obtain a mixture;
[0043] Step 2: Place the mixed material in a single screw extruder, extrude and shape at 180° C., cool and stretch to obtain a TPU composite film.
[0044] Example 2, Preparation of TPU composite film
[0045] Step 1, 70g of TPU resin with a hardness of 90A, 13g of environmentally friendly mist-slip masterbatch, 5.5g of diisopropylbenzene peroxide, 2.5g of ethylene glycol diethyl ether diaminetetraacetic acid, 9g of silicone-coated fiber, 11g of anti-UV toughening additive, 2.5g of p-toluenesulfonyl semicarbazide, 2g of antioxidant 1076, and 3g of 2-ethylhexyl diphenyl phosphate were placed in a high-speed mixer and mixed at a rate of 700r / min for 40min to obtain a mixture;
[0046] Step 2: Place the mixed material in a single screw extruder, extrude and shape at 190° C., cool and stretch to obtain a TPU composite film.
[0047] Example 3, Preparation of TPU composite film
[0048] Step 1, 80g of TPU resin with a hardness of 92A, 15g of environmentally friendly mist-slip masterbatch, 6g of diisopropylbenzene peroxide, 3g of ethylene glycol diethyl ether diaminetetraacetic acid, 10g of silicone-coated fiber, 12g of anti-ultraviolet toughening additive, 3g of sodium bicarbonate, 3g of antioxidant 168, and 5g of tetraethyl methylene diphosphonate were placed in a high-speed mixer and mixed at a rate of 800r / min for 45min to obtain a mixture;
[0049] Step 2: Place the mixed material in a single screw extruder, extrude and shape at 200° C., cool and stretch to obtain a TPU composite film.
[0050] Comparative Example 1
[0051] Preparation of TPU composite film
[0052] Step 1, 70g of TPU resin with a hardness of 90A, 13g of environmentally friendly mist-slip masterbatch, 5.5g of diisopropylbenzene peroxide, 2.5g of ethylene glycol diethyl ether diaminetetraacetic acid, 9g of modified medical stone fiber, 11g of anti-UV toughening additive, 2.5g of p-toluenesulfonyl semicarbazide, 2g of antioxidant 1076, and 3g of 2-ethylhexyl diphenyl phosphate were placed in a high-speed mixer and mixed at a rate of 700r / min for 40min to obtain a mixture;
[0053] Step 2: Place the mixed material in a single screw extruder, extrude and shape at 190° C., cool and stretch to obtain a TPU composite film.
[0054] Comparative Example 2
[0055] Preparation of TPU composite film
[0056] Step 1, 70g of TPU resin with a hardness of 90A, 13g of environmentally friendly mist-slip masterbatch, 5.5g of diisopropylbenzene peroxide, 2.5g of ethylene glycol diethyl ether diaminetetraacetic acid, 9g of silicone-coated fiber, 11g of polyvinyl butyral, 2.5g of p-toluenesulfonyl semicarbazide, 2g of antioxidant 1076, and 3g of 2-ethylhexyl diphenyl phosphate were placed in a high-speed mixer and mixed at a rate of 700r / min for 40min to obtain a mixture;
[0057] Step 2: Place the mixed material in a single screw extruder, extrude and shape at 190° C., cool and stretch to obtain a TPU composite film.
[0058] Comparative Example 3
[0059] Preparation of TPU composite film
[0060] Step 1, 70g of TPU resin with a hardness of 90A, 13g of environmentally friendly mist-slip masterbatch, 5.5g of diisopropylbenzene peroxide, 2.5g of ethylene glycol diethyl ether diaminetetraacetic acid, 9g of silicone-coated fiber, 11g of modified polyvinyl butyral, 2.5g of p-toluenesulfonyl semicarbazide, 2g of antioxidant 1076, and 3g of 2-ethylhexyl diphenyl phosphate were placed in a high-speed mixer and mixed at a rate of 700r / min for 40min to obtain a mixture;
[0061] Step 2: Place the mixed material in a single screw extruder, extrude and shape at 190° C., cool and stretch to obtain a TPU composite film.
[0062] Comparative Example 4
[0063] Preparation of TPU composite film
[0064] Step 1, 70g of TPU resin with a hardness of 90A, 13g of environmentally friendly mist-slip masterbatch, 5.5g of diisopropylbenzene peroxide, 2.5g of ethylene glycol diethyl ether diaminetetraacetic acid, 9g of silicone-coated fiber, 2.5g of p-toluenesulfonyl semicarbazide, 2g of antioxidant 1076, and 3g of 2-ethylhexyl diphenyl phosphate were placed in a high-speed mixer and mixed at a rate of 700r / min for 40min to obtain a mixture;
[0065] Step 2: Place the mixed material in a single screw extruder, extrude and shape at 190° C., cool and stretch to obtain a TPU composite film.
[0066] Comparative Example 5
[0067] Preparation of TPU composite film
[0068] Step 1, 70g of TPU resin with a hardness of 90A, 13g of environmentally friendly mist-slip masterbatch, 5.5g of diisopropylbenzene peroxide, 2.5g of ethylene glycol diethyl ether diaminetetraacetic acid, 11g of anti-UV toughening additive, 2.5g of p-toluenesulfonyl semicarbazide, 2g of antioxidant 1076, and 3g of 2-ethylhexyl diphenyl phosphate were placed in a high-speed mixer and mixed at a rate of 700r / min for 40min to obtain a mixture;
[0069] Step 2: Place the mixed material in a single screw extruder, extrude and shape at 190° C., cool and stretch to obtain a TPU composite film.
[0070] Performance Testing
[0071] The TPU composite films prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were made into samples that met the specifications, and the elongation at break and the tensile strength of the samples were tested using a CZ-4000D1 tensile testing machine at a wavelength of 313 nm and an irradiance of 0.72 / m 2 The tensile strength of the sample after aging treatment in the UV aging box; the water contact angle tester JC2000D2G was used to test the sample; the Vicat softening temperature of the sample was tested according to GB / T1633-2000 to determine the high temperature resistance of the sample; the wear resistance of the sample was tested using a Taber abrasion tester, two grinding wheels were placed on the sample, and the grinding wheel movement speed was set to 40r / min to perform a wear test on the sample, and the initial mass of the sample and the mass of the sample after 20,000 revolutions of wear were recorded, and the sample wear value was calculated using the following formula: m=m1-m2; where m is the sample wear value, g / 20,000r; m1 is the initial mass of the sample, g; m2 is the mass of the sample after grinding, g; the specific test results are shown in the table below:
[0072] It can be seen from the above table that the TPU films prepared in the examples have excellent toughness, tensile strength, wear resistance, UV resistance, waterproof performance and high temperature resistance, can meet the use requirements of TPU films in various environments, and have a long service life.
[0073] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0074] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A TPU foam film based on a composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of TPU resin, 10-15 parts of environmentally friendly mist-slip masterbatch, 5-6 parts of dicumyl peroxide, 2-3 parts of ethylene glycol diethyl ether diamine tetraacetic acid, 8-10 parts of silicone-coated fiber, 10-12 parts of anti-ultraviolet toughening additive, 2-3 parts of foaming agent, 1-3 parts of antioxidant, and 2-5 parts of flame retardant; The preparation method of the organosilicon-coated fiber comprises the following steps: S1: Place medical stone fiber in anhydrous ethanol, ultrasonically disperse for 10-15 minutes, introduce nitrogen, add chloroethyl isocyanate and catalyst, heat to 60-70°C for reaction for 2-3 hours, cool down, filter, wash and dry to obtain modified medical stone fiber; S2: Place the modified medical stone fiber in deionized water, perform ultrasonic dispersion treatment for 15-20 minutes, add amino-terminated silicone oil and triethylamine, heat to 80-85°C, stir for 12-18 hours, filter after cooling, wash, and dry to obtain silicone-coated fiber; The preparation method of the anti-ultraviolet toughening additive comprises the following steps: SS1: polyvinyl butyral, 3,4,9,10-perylenetetracarboxylic dianhydride and p-toluenesulfonic acid are placed in toluene, heated to 70-75°C for reaction for 6-8h, and the product is collected after reduced pressure distillation to obtain modified polyvinyl butyral; SS2: Modified polyvinyl butyral, 2,3,4,4'-tetrahydroxybenzophenone and p-toluenesulfonic acid are placed in N,N-dimethylformamide, the temperature is raised to react, and the product is collected after rotary evaporation to obtain an anti-ultraviolet toughening additive.
2. A TPU foam film based on a composite material according to claim 1, characterized in that: The hardness of the TPU resin is 88-92A; the foaming agent is any one of azodicarbonamide, p-toluenesulfonyl semicarbazide, and sodium bicarbonate; the antioxidant is any one of antioxidant 1010, antioxidant 1076, and antioxidant 168; the flame retardant is any one of diphenyl phosphate, 2-ethylhexyl diphenyl phosphate, and tetraethyl methylene diphosphonate.
3. A TPU foamed film based on a composite material according to claim 1, characterized in that: In step S1, the catalyst is any one of stannous octoate and dibutyltin dilaurate.
4. A TPU foamed film based on a composite material according to claim 1, characterized in that: In step S2, the viscosity of the amino-terminated silicone oil is 3000-10000 mPa·s.
5. A TPU foamed film based on a composite material according to claim 1, characterized in that: In step SS1, the molecular weight of the polyvinyl butyral is 30,000-45,000.
6. A TPU foamed film based on a composite material according to claim 1, characterized in that: In step SS2, the temperature of the temperature-raising reaction is 105-115° C., and the time is 5-8 hours.
7. A method for preparing a TPU foamed film based on a composite material as claimed in claim 1, characterized in that: The following steps are involved: Step 1, place TPU resin, environmentally friendly mist slip masterbatch, dicumyl peroxide, ethylene glycol diethyl ether diamine tetraacetic acid, silicone coated fiber, anti-ultraviolet toughening additive, foaming agent, antioxidant, flame retardant in a high-speed mixer, mix at a rate of 600-800r / min for 30-45min to obtain a mixture; Step 2: Place the mixed material in a single screw extruder, extrude and shape at 180-200° C., cool and stretch to obtain a TPU composite film.
Citation Information
Patent Citations
A heat-resistant and stable TPU film and preparation method thereof
CN117186623B
Polymer-based nano-composite material for headset wire and preparation method of polymer-based nano-composite material
CN104610726A
Thermographic recording material providing prints with good image density and tone having improved archivability
EP1245404A1